Stable Polarized del Pezzo Surfaces. (26th July 2018) - Cheltsov, Ivan; Martinez-Garcia, Jesus
Abstract: We give a simple sufficient condition for K -stability of polarized del Pezzo surfaces and for the existence of a constant scalar curvature Kähler metric in the Kähler class corresponding to the polarization.